2016
DOI: 10.3390/ijms17020223
|View full text |Cite
|
Sign up to set email alerts
|

Micellization Behavior of Long-Chain Substituted Alkylguanidinium Surfactants

Abstract: Surface activity and micelle formation of alkylguanidinium chlorides containing 10, 12, 14 and 16 carbon atoms in the hydrophobic tail were studied by combining conductivity and surface tension measurements with isothermal titration calorimetry. The purity of the resulting surfactants, their temperatures of Cr→LC and LC→I transitions, as well as their propensity of forming birefringent phases, were assessed based on the results of 1H and 13C NMR, differential scanning calorimetry (DSC), and polarizing microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Temperature change affects the micellization of ionic and amphoteric surfactants due to the relative change in the interaction of the hydrophobic and hydrophilic groups in the surfactant. critical micelle concentration is a distinguishing characteristic property of surfactants as well as the Krafft temperature which is defined as the minimum temperature at which micellization occurs (22).The aim of this work is to find out some new properties of surfactants that is created under the influence of magnetic water and the study of the effects of some alcohols on the micellization process of Tweens surfactant.…”
Section: Department Of Chemistry College Of Education Formentioning
confidence: 99%
“…Temperature change affects the micellization of ionic and amphoteric surfactants due to the relative change in the interaction of the hydrophobic and hydrophilic groups in the surfactant. critical micelle concentration is a distinguishing characteristic property of surfactants as well as the Krafft temperature which is defined as the minimum temperature at which micellization occurs (22).The aim of this work is to find out some new properties of surfactants that is created under the influence of magnetic water and the study of the effects of some alcohols on the micellization process of Tweens surfactant.…”
Section: Department Of Chemistry College Of Education Formentioning
confidence: 99%
“…Bouchal et al. studied the micellization behavior of alkylguanidinium chlorides containing 10, 12, 14 and 16 carbon atoms in the hydrophobic tail, being these compounds less soluble in water and more surface‐active than the analogous alkyltrimethylammonium bromides or chlorides.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the imidazolium family, other types of SAILs have also been investigated, namely ammonium-, [35][36][37][38] phosphonium-, [23] morpholinium-, [38][39][40][41] and guanidinium-based SAILs. [42][43][44] Brown et al [35] reported a series of IL-based surfactants composed of tetraalkylammonium cations and common surfactant anions (derived from dodecyl sulfate and aerosol-OT) as alternatives to imidazolium-based systems, being claimed as cheaper and environmentally more benign. More recently, a series of mono and dicationic ammonium bromide ILs were synthetized and studied by Özdil and co-workers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations